ACTIVATION OF BUTYRYLCHOLINESTERASE ENZYME BY MAGNESIUM IONS - Elkhashab, R. A. (European Scientific Journal, ESJ, 2013)
Human serum Butyrylcholinesterase (BChE) is an important enzyme in detoxification with its capacity for hydrolyzing esters. the inhibition of this enzyme lead to ill health. The reaction of enzyme with metals ions have grown in recent years,. in our study we examine the reaction of Mg+2 with normal and toxic form of enzyme .we collected samples as two groups for normal and toxic plasma, treated with different concentration of Mg+2 , compare the reading of plasma cholinesterase before and after treating , there are significant changing for that two groups at certain Mg+2 concentration. this changing may be for the allosteric effect of cholinesterase enzyme , reformation the binding site as its environment changing .